PREDISPOSING FACTORS TO EXTRAMARITAL SEXUAL BEHAVIOUR AMONG MARRIED MEN IN IBADAN NORTH LOCAL GOVERNMENT AREA, NIGERIA (2012)
In Nigeria there is anecdotal evidence that married men are more likely to engage in extramarital sexual intercourse than married women. The predisposing factors to this social phenomenon have however not been systematically investigated enough. This study was therefore aimed at identifying factors that predispose married men to extramarital sexual activities in Ibadan North Local Government Area (LGA). The study was a descriptive cross-sectional survey. A 3-stage sampling technique was used to select 400 married men from workplaces in six of the twelve wards in the LGA. Data were collected using pre-tested semi-structured questionnaire and Focus Group Discussion (FGD) guide. Six FGDs were conducted with each comprising eight participants. Qualitative data were analyzed using thematic approach while quantitative data were analyzed using descriptive statistics and Chi-square at 5% level of significance. The mean age of the respondents was 38.8 ± 8.7 years, 89.3% were Yoruba, 50.5% were Christians, and more (45.0%) of the respondents had secondary education. Majority (73.8%) of the respondents were in monogamous unions. Thirty-seven percent had ever had extramarital sexual relationship and of this 59.1% were in monogamous union. Few (23.1%) engaged in the act when their wives traveled while 76.9% did so even when their wives were available. Only 8.8% used a condom during extramarital sexual acts. Reasons for involvement in extramarital sexual relationship included: need for variety of sexual experiences (28.2%), lack of emotional relationship with spouse (25.6%), apathy towards spouse at home (15.4%) and inability to have male children (7.7%). The FGD participants were of the view that factors that promote extramarital practices among married men were: irreconcilable differences, sexual discontentment, frequent marital disputes orchestrated by the wife’s nagging behaviour, covetousness, and wife’s absence from home for a long period of time and renewal of relationship with pre-marital female friends. Consequences of extramarital sexual relationship listed included risks of transmitting Sexually Transmitted Infections (STIs) to spouse and reduced financial commitment by husband towards family up-keep. Perceived outcome risks of involvement in extramarital affairs included: divorce (7.3%), STIs (6.2%), sudden death (2.5%) and physical attack by the spouse of concubine (0.8%). Only 16.9% of respondents who had been having extramarital sexual relationship perceived themselves vulnerable to STIs. Extramarital sexual practices existed among 29.1% respondents who were living with their spouses, 39.8% who were not living with spouses and 82.4% who did not disclosed the whereabouts of their spouses and this was significantly related. Prevalence of extramarital sexual relationship significantly increased with level of education as follows: 21.0% (primary), 28.3% (secondary) and 62.4% (tertiary). The prevalence of extramarital sexual behaviour was relatively high among the respondents with psycho-social needs being the main predisposing factors. Public enlightenment and marital guidance and counseling services are needed to ameliorate this situation.